The impact of a visit to Lesotho Water and Sewage Authority (WASA) on learner's knowledge about community health - Molahloe, Maretsepile Relebohile (My University, 2012)
There is an increasing adoption of outdoor visits in high schools in Lesotho and this study was done to find out what students learn about community health as they visit Lesotho Water and Sewage Authority (WASA). Eighty Form D (equivalent to grade 11 in South Africa) learners were the participants in this study. In order to capture students‘ learning a qualitative study was designed. The study used observations, questionnaire (n=80) and semi-structured interviews (n=8) with learners. The data was analyzed inductively and deductively in order to answer questions about knowledge changes as a result of a visit to WASA, and about the aspects of the visit that influence learners‘ knowledge about community health. Analysis of the questionnaire and the interviews revealed that learners greatly gained knowledge as a result of the visit to WASA while others developed misconception and others did not change their conceptions at all. The forms of conceptual change identified from learners responses were enrichment and conceptual capture. Learners realized that water purification is not a minute-made activity since there are several steps involved in water purification and that taps are not the main water sources. Learners also became aware that boiling water is not the only effective way of treating water instead other purifying stations like WASA can purify water suitable for domestic use. However, some learners believed that water that has been treated by the sewage plant is not suitable to be purified and used for domestic purpose. The observation analysis indicated that the physical facilities, displays, prior knowledge and participation during the visit are some of the aspects that influence learners‘ knowledge about community health. The realism of concepts communicated during the visit enhanced learners‘ ability to acquire knowledge about community health. The physical facilities such as the machinery at WASA provided the concrete evidence that water is drawn from the rivers therefore rivers are the main water sources. Visual displays contributed much in learners‘ ability to gain knowledge during the visit to WASA. It has also been found that although manipulation of objects was minimal, learners still gained information communicated during the visit. With the stated findings above, a visit to WASA enhance learner‘s ability to acquire information about community health.
MSc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Community health services; Public health; Environmental health